2005
DOI: 10.1029/2005gl023155
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave tomography from microseisms in Southern California

Abstract: Since it has already been demonstrated that point‐to‐point seismic propagation Green Functions can be extracted from seismic noise, it should be possible to image Earth structure using the ambient noise field. Seismic noise data from 148 broadband seismic stations in Southern California were used to extract the surface wave arrival‐times between all station pairs in the network. The seismic data were then used in a simple, but densely sampled tomographic procedure to estimate the surface wave velocity structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
379
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 551 publications
(391 citation statements)
references
References 22 publications
5
379
1
6
Order By: Relevance
“…The maps agreed very well with the known geology of the region, for example low velocity anomalies are co-located with sedimentary basins such as the San Joaquin Basin, and high velocity anomalies are associated with the igneous mountain ranges such as the Sierra Nevada. Almost simultaneously, Sabra et al (2005b) produced interferometric surface waves by crosscorrelating 18 days of ambient noise recorded on 148 stations in southern California. The tomographic maps they produced agree well with the known geology and previous seismic studies in the region.…”
Section: Ambient Noise Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…The maps agreed very well with the known geology of the region, for example low velocity anomalies are co-located with sedimentary basins such as the San Joaquin Basin, and high velocity anomalies are associated with the igneous mountain ranges such as the Sierra Nevada. Almost simultaneously, Sabra et al (2005b) produced interferometric surface waves by crosscorrelating 18 days of ambient noise recorded on 148 stations in southern California. The tomographic maps they produced agree well with the known geology and previous seismic studies in the region.…”
Section: Ambient Noise Tomographymentioning
confidence: 99%
“…The tomographic maps they produced agree well with the known geology and previous seismic studies in the region. Since then, surface wave tomography using interferometric Rayleigh and Love waves, commonly referred to as ambient noise tomography, has become an increasingly employed method to successfully produce subsurface velocity models on regional and continental scales in areas such as the United States (Bensen et al, 2008; Lin et al, 2008;Shapiro et al, 2005;Sabra et al, 2005b;Liang and Langston, 2008), Australia (Arroucau et al, 2010;Rawlinson et al, 2008;Saygin and Kennett, 2010), New Zealand (Lin et al, 2007;Behr et al, 2010), Antarctica (Pyle et al, 2010), Iceland (Gudmundsson et al, 2007), China (Zheng et al, 2008;Li et al, 2009;Zheng et al, 2010), South Africa , Europe (Villaseñ or et al, 2007;Yang et al, 2006), South Korea (Cho et al, 2007) the Tibetan Plateau (Yao et al, 2006(Yao et al, , 2008Li et al, 2009), and in this paper, Scotland.…”
Section: Ambient Noise Tomographymentioning
confidence: 99%
“…Experimental and theoretical studies have demonstrated that an estimate of the arrival time structure between two receivers, for a given acoustic or elastic medium (as determined by the Green's function between the receivers locations) can be obtained from the time-averaged cross correlation of the ambient noise recorded by the two receivers. This has been shown among others in the fields of ultrasonics [Weaver and Lobkis, 2001;Larose et al, 2004;Lani et al, 2011], helioseismology [Duvall et al, 1993;Rickett and Claerbout, 1996], seismology [Sabra et al, 2005a;Shapiro et al, 2005;Brenguier et al, 2007], structural health monitoring [Sabra and Huston, 2011;Snieder and Cafak, 2006;Larose et al, 2007;Farrar and James, 1997], and elastography [Sabra and Archer, 2009;Sabra et al, 2007]. For instance, ambient noise correlation processing has successfully been used to continuously monitor with unprecedented temporal resolution seismically active systems such as fault zones [Brenguier et al, 2008] and volcanic areas [Brenguier et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Notable research in advancing the use of ambient noise in passive applications of SHM evolved out of leading research work in ocean acoustic and seismology [16][17][18][19]. The advantage to using existing noise sources in the ocean removes the limitations and barriers of active sonar that create concerns for ocean wildlife.…”
Section: Introductionmentioning
confidence: 99%